An experimental investigation of various trickle collector structures to enhance solar water heater efficiency - Nugroho Agung Pambudi; Iksan Riva Nanda; Alisya Eka Putri; Robby Nur Salsala; Muhammad Aziz; Bayu Rudiyanto; Apri Wiyono (Cleaner Engineering and Technology, 2024)
This study aimed to enhance the efficiency of the solar water heater (SWH) due to the increasing demand of renewable energy. It compared use three different solar collector models, namely Model A (square-shaped polycarbonate), Model B (v-corrugated zinc), and Model C (trapezoidal aluminium) to identify the most cost-effective configuration. The models were subjected to experiments in real operating conditions during the summer season in Indonesia. Various parameters, including solar radiation intensity, wind speed, inlet and outlet temperatures, and flow rate, were measured every 10 min from morning to afternoon. Additionally, the study employed a trickle and one-way flow rate system. The results showed that Model B achieved the highest total efficiency at 50%, followed by Models A and C at 47% and 34%, respectively. The 120 Lph flow rate exhibited better performance in absorbing useful heat energy than the 240 Lph flow rate. Based on these findings, all three models were recommended for the household-scale SWH applications. Model A showed the most promising economic value but had a shorter lifespan due to the tendency of polycarbonate to deform. In contrast, Model B and Model C, using zinc and aluminium, offered longer lifespans.